2009
DOI: 10.1097/fjc.0b013e3181bad042
|View full text |Cite
|
Sign up to set email alerts
|

Intrapericardial Delivery of Amiodarone and Sotalol: Atrial Transmural Drug Distribution and Electrophysiological Effects

Abstract: Amiodarone and sotalol are frequently used in the treatment of atrial fibrillation. However, oral and intravenous (IV) therapy with these drugs has suboptimal efficacy and is associated with serious extracardiac side effects. We hypothesized that intrapericardial (IPC) delivery produces antiarrhythmic effects at lower plasma drug concentrations than IV delivery. Goats (n = 27) were randomised into 5 groups receiving either IPC vehicle, amiodarone (IV or IPC) or dl-sotalol (IV or IPC). Epicardial and endocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…To improve the effectiveness of drugs and minimize their systemic toxicity, 3 alternative applications for epicardial amiodarone delivery have been developed: IPC-infused amiodarone solutions, epicardially sprayed in situ amiodarone releasing adhesive hydrogels, and epicardially sutured amiodarone-eluting bilayered patches or disc. [19][20][21] A number of studies have investigated local drug delivery of antiarrhythmic agents, including lidocaine, digoxin, amiodarone, beta-blockers, procainamide, ibutilide, sotalol, and flecainide. 17,21,22 Pharmacokinetic advantages and significant effects on atrial electrophysiologic parameters were invariably demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the effectiveness of drugs and minimize their systemic toxicity, 3 alternative applications for epicardial amiodarone delivery have been developed: IPC-infused amiodarone solutions, epicardially sprayed in situ amiodarone releasing adhesive hydrogels, and epicardially sutured amiodarone-eluting bilayered patches or disc. [19][20][21] A number of studies have investigated local drug delivery of antiarrhythmic agents, including lidocaine, digoxin, amiodarone, beta-blockers, procainamide, ibutilide, sotalol, and flecainide. 17,21,22 Pharmacokinetic advantages and significant effects on atrial electrophysiologic parameters were invariably demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…1-2 orders of magnitude lower than levels normally present during intravenous or chronic oral amiodarone therapy. In a recent study in our laboratory, we showed that transmural drug concentration gradients during intrapericardial delivery of amiodarone were not only present in ventricles, but also in atria [9]. Although epicardial and endocardial atrial ERPs were both prolonged, the absolute difference between them (transmural dispersion of refractoriness) did not increase.…”
Section: Discussionmentioning
confidence: 95%
“…Measurements were performed during the surgical procedure and 1, 2, 3,4,7,9,11,14,16,18,21,23,25 and 28 days after the surgical procedure. An electrophysiology monitoring system with an integrated amplifier/stimulator (EPTracer 38, CardioTek, Maastricht-Airport, The Netherlands) was used to simultaneously record limb-lead ECG and six bipolar electrograms from the 3 silicone patches sutured to the right atrial lateral wall.…”
Section: Electrophysiological Protocolsmentioning
confidence: 99%
See 2 more Smart Citations